An anti-adhesive, anti-coagulant, lubricious coating material and its preparation method and use

CN122998482APending Publication Date: 2026-10-30SHANDONG WEIGAO GROUP MEDICAL POLYMER +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611324135.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]现有血液透析针涂层技术存在以下明显不足:(1)现有涂层的功能单一,不兼备润滑性能、抗黏附性能和抗凝血功能

Benefits of technology

[0017]与现有技术相比,本发明提供了一种抗黏附抗凝血润滑涂层材料的制备方法,包括如下步骤:A)在保护气体氛围下,式(I)结构的含氟丙烯酸酯单体、式(II)结构的聚二甲基硅氧烷-胺、三乙胺和溶剂混合进行反应,得到含氟硅氧烷共聚物;B)在保护气体氛围下,式(III)结构的磷酰胆碱衍生物、式(IV)结构的聚二甲基硅氧烷-胺、三乙胺和溶剂混合进行反应,沉淀洗涤、干燥得到磷酰胆碱硅氧烷共聚物;C)将步骤A)得到的含氟硅氧烷共聚物和步骤B)得到的磷酰胆碱硅氧烷共聚物溶于溶剂中,混合后得到抗黏附抗凝血润滑涂层材料。本发明通过分子结构设计和组分比例的优化调控,在保持优异润滑性能的同时,赋予涂层高效的抗凝血、抗黏附功能,单次浸涂简化了涂覆工艺,涂层与金属表面交联反应增强了涂层稳定性,进入血液前后,可实现干态润滑与湿态抗凝血功能切换。进入血液前,磷酰胆碱硅氧烷链段收缩,含氟硅氧烷链段发挥润滑及抗细菌粘附功能,进入血液后,含氟硅氧烷链段收缩,磷酰胆碱硅氧烷链段发挥抗蛋白质黏附及抗凝血功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a preparation method of an anti-adhesion anticoagulant lubricating coating material, and comprises the following steps: mixing fluorine-containing propylene acrylate monomers, polydimethylsiloxane-amine, triethylamine and a solvent to react under a protective gas atmosphere to obtain a fluorine-containing siloxane copolymer; mixing phosphorylcholine derivatives, polydimethylsiloxane-amine, triethylamine and a solvent to react under a protective gas atmosphere, and then performing precipitation, washing and drying to obtain a phosphorylcholine siloxane copolymer; and the two copolymers are dissolved in a solvent and uniformly mixed to obtain a target coating material. The material is optimized in terms of molecular structure and proportion, and has the characteristics of lubrication, anticoagulation and anti-adhesion. The material can be crosslinked with metal by using a single immersion coating process, can improve stability, can realize dry-state lubrication and wet-state anticoagulation function switching, and can realize lubrication, antibacterial adhesion and anti-protein adhesion in a blood environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical materials technology, and in particular to an anti-adhesion and anticoagulant lubricating coating material, its preparation method, and its application. Background Technology

[0002] Surface modification technology for blood-contact medical devices is a research hotspot in the field of biomedical materials. For metallic medical devices and components, such as hemodialysis needles, the surface properties directly affect operational safety and the stability of blood components. When these devices enter the bloodstream, they are prone to operational injuries, infections, and thrombosis.

[0003] Currently, the most commonly used lubrication system for hemodialysis needles is silicone oil coating. Non-reactive silicone oil coatings adhere to the needle surface through physical adsorption, but their force is weak. Under the dynamic flushing of high-flow blood over a long period, the silicone oil is easily washed away or migrated, leading to a rapid decline in lubrication performance, increasing puncture resistance and the risk of tissue damage. Detached silicone oil particles may enter the bloodstream, posing a potential risk of embolism or inflammatory reactions. Reactive silicone oil coatings form covalent bonds with the needle surface, exhibiting significantly better erosion resistance than non-reactive silicone oils. However, blood compatibility remains insufficient. Silicone oil itself has hydrophobic and hemophobic properties, and the cured coating surface can easily induce platelet adhesion and activation, thereby triggering a coagulation cascade reaction and increasing the risk of thrombosis.

[0004] On the other hand, to improve the blood compatibility of blood-contact medical devices, researchers have developed various anticoagulant coatings, such as heparin and phosphorycholine. However, existing anticoagulant coatings generally suffer from insufficient lubrication. Hydrophilic anticoagulant materials have a high surface friction coefficient, resulting in high resistance during puncture, which not only aggravates patient pain but may also cause damage to the vascular endothelium, increasing the incidence of bleeding and hematoma at the puncture site. Patent CN113372494B discloses an anticoagulant polymer coating material obtained through emulsion polymerization or solution polymerization. Its anticoagulant component is heparin, which is covalently bonded to the coating. This coating has good adhesion and wet and dry fastness to plastic substrates, but there is no chemical cross-linking reaction between the coating and the metal substrate, resulting in insufficient interfacial bonding. After sterilization, the coating is prone to peeling off and failure, and it lacks lubrication and anti-adhesion properties.

[0005] The existing coating technology for hemodialysis needles has the following obvious shortcomings: (1) The existing coatings have a single function and do not have lubrication, anti-adhesion and anticoagulation functions. Pure lubrication coatings have insufficient erosion resistance and blood compatibility; pure anticoagulation coatings can inhibit coagulation, but lack effective lubrication function and cannot meet the requirements of puncture smoothness and stability under blood flow erosion environment. Under high flow dynamic blood erosion conditions, single-function coatings are difficult to maintain long-lasting lubrication and long-term anticoagulation performance at the same time. (2) The two or more dip coating processes lead to complicated preparation process and low production efficiency. (3) After sterilization, the interfacial bonding force between coatings is insufficient, which easily leads to the coating peeling off and failing during use. Summary of the Invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing an anti-adhesion and anticoagulant lubricating coating material. The coating material provided by the present invention provides a method for forming a stable coating on the surface in a single coating application. Through a condensation reaction, it firmly bonds to the metal surface to form a stable coating. At the same time, it introduces lubricating components, anti-adhesion components, and anticoagulant active components with synergistic effects to construct a multifunctional composite coating system. Before and after entering the bloodstream, it can achieve switching between dry lubrication and wet anticoagulant functions. This coating material provides excellent lubrication performance while achieving anti-adhesion and anticoagulant functions, significantly improving the anticoagulant performance of blood contact devices.

[0007] This invention provides a method for preparing an anti-adhesion and anticoagulant lubricating coating material, comprising the following steps: A) Under a protective gas atmosphere, a fluorinated acrylate monomer of formula (I), a polydimethylsiloxane-amine of formula (II), triethylamine and a solvent are mixed and reacted to obtain a fluorinated siloxane copolymer; B) Under a protective gas atmosphere, the phosphorylcholine derivative of formula (III), the polydimethylsiloxane-amine of formula (IV), triethylamine and solvent are mixed and reacted, and the precipitate is washed and dried to obtain the phosphorylcholine siloxane copolymer. C) Dissolve the fluorinated siloxane copolymer obtained in step A) and the phosphorylcholine siloxane copolymer obtained in step B) in a solvent, and mix them to obtain an anti-adhesion and anticoagulant lubricating coating material; Formula (I); Formula (II); Formula (III); Formula (IV); Where R represents H or CH3, m≥1, n≥1; R1 and R2 independently represent H or OCH3, A independently represents a group containing an amino group, a is an integer from 30 to 300, b is an integer from 1 to 100, a:b=5~100:1, and the weight-average molecular weight is 1000~20000; R5 represents an epoxy group, isocyanate group, or acryloyl group, R3 and R4 independently represent H or OCH3, B independently represents a group containing an amino group, c is an integer from 50 to 400, d is an integer from 5 to 150, c:d=5~100:1, and the weight-average molecular weight is 3000~30000.

[0008] In some embodiments, the fluorinated acrylate monomer is one or more of dodecafluoroheptyl methacrylate, 1H,1H,2H,2H-heptadecane acrylate, and 1H,1H,2H,2H-perfluorodecyl acrylate.

[0009] In some embodiments, the molar ratio of the fluorinated acrylate monomer, polydimethylsiloxane-amine and triethylamine in step A) is 1:1~20:0.01~0.1.

[0010] In some embodiments, the protective gas in step A) is one of nitrogen, argon, helium, and neon; The solvent is one of tetrahydrofuran, toluene, ethanol, and acetone; The reaction temperature is 60~80℃ and the reaction time is 6~12h; the reaction is followed by washing and rotary evaporation; the washing solvent is deionized water.

[0011] In some embodiments, the phosphorylcholine derivative in step B) is one or more of 2-isocyanate ethyl phosphorylcholine, 2-epoxypropyloxyethyl phosphorylcholine, and 2-methacryloyloxyethyl phosphorylcholine.

[0012] In some embodiments, the molar ratio of the phosphorylcholine derivative, polydimethylsiloxane-amine and triethylamine in step B) is 1:0.01-0.5:0.01~0.1.

[0013] In some embodiments, the protective gas in step B) is one of nitrogen, argon, helium, and neon; The solvent is one of anhydrous methanol, anhydrous ethanol, and trifluoroethanol; the reaction temperature is 50~70℃, and the reaction time is 12~24h; the washing reagent is acetone, and the washing is performed 3~5 times.

[0014] In some embodiments, the mass ratio of the fluorinated siloxane copolymer obtained in step C) to the phosphorylcholine siloxane copolymer obtained in step B) is 1:1.5.

[0015] This invention provides an anti-adhesion and anticoagulant lubricating coating material, which is prepared by any one of the preparation methods described in the above technical solutions.

[0016] This invention provides the application of the anti-adhesion and anticoagulant lubricating coating material prepared by any of the above-described preparation methods, or the anti-adhesion and anticoagulant lubricating coating material described in the above-described technical solutions, in the preparation of blood contact medical devices.

[0017] Compared with existing technologies, this invention provides a method for preparing an anti-adhesion and anticoagulant lubricating coating material, comprising the following steps: A) Under a protective gas atmosphere, a fluorinated acrylate monomer of formula (I), a polydimethylsiloxane-amine of formula (II), triethylamine, and a solvent are mixed and reacted to obtain a fluorinated siloxane copolymer; B) Under a protective gas atmosphere, a phosphorylcholine derivative of formula (III), a polydimethylsiloxane-amine of formula (IV), triethylamine, and a solvent are mixed and reacted, precipitated, washed, and dried to obtain a phosphorylcholine siloxane copolymer; C) The fluorinated siloxane copolymer obtained in step A) and the phosphorylcholine siloxane copolymer obtained in step B) are dissolved in a solvent, and after mixing, an anti-adhesion and anticoagulant lubricating coating material is obtained. This invention, through molecular structure design and optimized control of component ratios, endows the coating with efficient anticoagulant and anti-adhesion functions while maintaining excellent lubrication performance. Single-dip coating simplifies the coating process, and the cross-linking reaction between the coating and the metal surface enhances the coating stability. Before and after entering the bloodstream, it can achieve switching between dry lubrication and wet anticoagulant functions. Before entering the bloodstream, the phosphorylcholine siloxane segments contract, and the fluorinated siloxane segments exert lubricating and antibacterial adhesion functions. After entering the bloodstream, the fluorinated siloxane segments contract, and the phosphorylcholine siloxane segments exert antiprotein adhesion and anticoagulant functions. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the anti-adhesion and anticoagulant lubricating coating prepared in Example 1, and its chain segment states before and after entering the bloodstream. Figure 2 This is a dot plot of the friction coefficient of a metal pipe after being coated with the anti-adhesion, anticoagulant, and lubricating coating material prepared in Example 1. Figure 3 This is a bar chart showing the puncture force of a hemodialysis needle after being coated with the anti-adhesion, anticoagulant, and lubricating coating material prepared in Example 1. Figure 4 Photographs of antibacterial adhesion plates of metal sheets (a) and uncoated metal sheets (b) after the anti-adhesion, anticoagulant and lubricating coating material prepared in Example 1 has been drop-coated into a film; Figure 5 This is a bar chart of Example 1 showing the amount of BSA adsorbed on the surface of a metal sheet determined by reading the OD value at 562 nm. Figure 6 This is a bar chart of Example 1 showing the coagulation index of a metal strip determined by measuring the absorbance of hemoglobin. Detailed Implementation

[0019] This invention provides an anti-adhesion, anticoagulant, and lubricating coating material, its preparation method, and its application. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and fall within the scope of this invention. The method and application of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the method and application described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

[0020] This invention provides a method for preparing an anti-adhesion and anticoagulant lubricating coating material, comprising the following steps: A) Under a protective gas atmosphere, a fluorinated acrylate monomer of formula (I), a polydimethylsiloxane-amine of formula (II), triethylamine and a solvent are mixed and reacted to obtain a fluorinated siloxane copolymer; B) Under a protective gas atmosphere, the phosphorylcholine derivative of formula (III), the polydimethylsiloxane-amine of formula (IV), triethylamine and solvent are mixed and reacted, and the precipitate is washed and dried to obtain the phosphorylcholine siloxane copolymer. C) Dissolve the fluorinated siloxane copolymer obtained in step A) and the phosphorylcholine siloxane copolymer obtained in step B) in a solvent, and mix them to obtain an anti-adhesion and anticoagulant lubricating coating material; Formula (I); Formula (II); Formula (III); Formula (IV); Where R represents H or CH3, m≥1, n≥1; R1 and R2 independently represent H or OCH3, A independently represents a group containing an amino group, a is an integer from 30 to 300, b is an integer from 1 to 100, a:b=5~100:1, and the weight-average molecular weight is 1000~20000; R5 represents an epoxy group, isocyanate group, or acryloyl group, R3 and R4 independently represent H or OCH3, B independently represents a group containing an amino group, c is an integer from 50 to 400, d is an integer from 5 to 150, c:d=5~100:1, and the weight-average molecular weight is 3000~30000.

[0021] The method for preparing the anti-adhesion and anticoagulant lubricating coating material provided by the present invention first involves reacting a mixture of a fluorinated acrylate monomer of formula (I), a polydimethylsiloxane-amine of formula (II), triethylamine, and a solvent under a protective gas atmosphere to obtain a fluorinated siloxane copolymer.

[0022] Formula (I); R represents H or CH3, m≥1, n≥1; specifically, m can be an integer from 1 to 12, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and n can be an integer from 1 to 12, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. The fluorinated acrylate monomers described in this invention are preferably one or more of dodecafluoroheptyl methacrylate, 1H,1H,2H,2H-heptadecane acrylate, and 1H,1H,2H,2H-perfluorodecyl acrylate, more preferably 1H,1H,2H,2H-perfluorodecyl acrylate; all of the above monomers have active groups that can react with amino groups and can be readily incorporated into copolymer segments.

[0023] In step A of this invention, the polydimethylsiloxane-amine is a compound with the structure of formula (II), where R1 and R2 independently represent H or OCH3, and A independently represents a group containing an amino group, such as -(CH2)3NH- or -(CH2)3NH(CH2)2NH-. The amino group can undergo an addition reaction with the active group of the fluorinated acrylate monomer, introducing the polydimethylsiloxane segment into the copolymer structure. The polydimethylsiloxane segment itself has excellent lubricating properties, which can effectively reduce the surface friction coefficient of the coating in the dry state and reduce the resistance during puncture. At the same time, the introduction of the fluorocarbon segment further improves the surface hydrophobicity and chemical inertness of the coating, giving the coating excellent antibacterial adhesion ability in the dry state and reducing the risk of bacterial implantation infection during puncture.

[0024] In this invention, the molar ratio of the fluorinated acrylate monomer, polydimethylsiloxane-amine and triethylamine in step A) is 1:1~20:0.01~0.1; preferably 1:1~10:0.01~0.05, and more preferably 1:1~5:0.03. For example, ratios can be 1:5:0.05, 1:12:0.08, 1:1:0.01, 1:2:0.02, 1:3:0.03, 1:4:0.04, 1:5:0.05, 1:6:0.06, 1:7:0.07, 1:8:0.08, 1:9:0.09, 1:10:0.10, 1:11:0.01, 1:12:0.02, 1:13:0.03, 1:14:0.04, 1:15:0.05, 1:16:0.06, 1:17:0.07, 1:18:0.08, 1:19:0.09, 1:20:0.10, and any intermediate ratio within the above ranges. The ratio can be adjusted according to the actual reactivity to ensure that the amino group fully participates in the reaction.

[0025] In this invention, when the molar ratio of fluorinated acrylate monomers to polydimethylsiloxane-amine is greater than 1:1, the hydrophilicity of the resulting antibacterial and hemostatic material decreases, and it cannot be uniformly dispersed in the solvent; when the molar ratio of fluorinated acrylate monomers to polydimethylsiloxane-amine is less than 1:20, the fluorine content of the anti-adhesion and anticoagulant material is too low, and it cannot effectively reduce the surface energy of the material.

[0026] The mass-to-volume ratio of the fluorinated acrylate monomer to the solvent is 0.1g:30-50mL, preferably 0.1g:35-45mL, and more preferably 0.1g:40mL.

[0027] Triethylamine acts as a catalyst to accelerate the addition reaction. The protective gas is one of nitrogen, argon, helium, or neon; any commonly used inert protective gas in the art can be used to achieve this invention, and no limitation is made here. The solvent is preferably one of tetrahydrofuran, toluene, ethanol, or acetone to ensure sufficient dissolution and dispersion of the reactants. Tetrahydrofuran or toluene is preferred, and toluene is more preferred.

[0028] The reaction temperature is 60-80℃, preferably 62-75℃, and more preferably 65℃; the reaction time is 6-12h, preferably 10-12h, and more preferably 12h; for example, the reaction can be carried out at 70℃ for 8h, 65℃ for 10h, and 75℃ for 9h. Within the above temperature and time range, the reaction can be ensured to proceed fully and will not lead to overpolymerization and abnormal product properties. After the reaction is completed, unreacted monomers and catalysts are removed by washing with deionized water, and then the solvent is removed by rotary evaporation to obtain the fluorosiloxane copolymer product.

[0029] The reaction is followed by washing and rotary evaporation; the washing solvent is deionized water, used to remove unreacted monomers and triethylamine salts to obtain purified fluorosiloxane copolymers. 'a' is an integer from 30 to 300, 'b' is an integer from 1 to 100, a:b = 5 to 100:1, and the weight-average molecular weight is 1000 to 20000; specifically, 'a' can be selected from 30, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, and 300, and specifically, 'b' can be selected from 1, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, and 100. The ratio of a to b can be selected from 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, and 100:1. The weight-average molecular weight can be selected from 1000, 2000, 3000, 5000, 8000, 10000, 12000, 15000, 18000, 20000, and any intermediate or range value within the above ranges.

[0030] Preferably, R1 and R2 independently represent OCH3, where a is an integer from 40 to 200, b is an integer from 10 to 50, a:b = 5 to 40:1, and the weight-average molecular weight is 2000 to 12000. More preferably, a is an integer from 140 to 200, b is an integer from 10 to 30, a:b = 5 to 20:1, and the weight-average molecular weight is 5000 to 10000. In some embodiments, a:b can be 20 to 80:1; in some specific embodiments, a is 100, b is 5, and a:b is 20:1.

[0031] Fluorinated acrylate monomers have a large number of fluorinated groups on their side chains. The low surface energy of the fluorinated side chains can give the coating excellent lubrication and anti-adhesion properties, effectively reduce the coefficient of friction of the coating surface, and reduce the adsorption and adhesion of proteins, bacteria and blood components.

[0032] The polydimethylsiloxane-amine of formula (II) has a siloxane backbone and good lubricity. Meanwhile, the reactive siloxane groups of the side chains can undergo condensation crosslinking with the substrate surface during the subsequent film formation process, thereby improving the bonding stability between the coating and the substrate.

[0033] Under a protective gas atmosphere, a phosphorylcholine derivative of formula (III), a polydimethylsiloxane-amine of formula (IV), triethylamine and a solvent are mixed and reacted. The precipitate is washed and dried to obtain a phosphorylcholine siloxane copolymer.

[0034] Formula (III); R5 represents an epoxy group, an isocyanate group, or an acryloyl group, preferably an acryloyl group.

[0035] The active group of R5 can react with the amino group of the polydimethylsiloxane-amine side chain to introduce a phosphorylcholine group into the copolymer structure. The phosphorylcholine group is a typical anticoagulant functional group with a biomimetic cell membrane structure, which can effectively inhibit protein adsorption and platelet adhesion, thereby achieving excellent anticoagulant effects.

[0036] Formula (IV); R3 and R4 independently represent H or OCH3, B independently represents a group containing an amino group, which can also be -(CH2)3NH- or -(CH2)3NH(CH2)2NH-, c is an integer from 50 to 400, d is an integer from 5 to 150, c:d = 5 to 100:1, and the weight-average molecular weight is 3000 to 30000; specifically, c can be selected from 50, 80, 100, 150, 200, 250, 300, 350, and 400, and d can be selected from... 5, 10, 20, 30, 50, 80, 100, 120, 150, where c:d can be specifically selected from 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, and the weight-average molecular weight can be specifically selected from 3000, 5000, 8000, 10000, 15000, 20000, 25000, 30000, and any intermediate or range value within the above ranges.

[0037] Preferably, R3 and R4 independently represent OCH3, c is an integer from 100 to 300, d is an integer from 10 to 80, c:d = 5 to 40:1, and the weight-average molecular weight is 5000 to 25000. More preferably, c is an integer from 150 to 250, d is an integer from 15 to 40, c:d = 5 to 20:1, and the weight-average molecular weight is 10000 to 20000. Preferably, R3 and R4 independently represent OCH3, c is an integer from 100 to 250, d is an integer from 10 to 80, c:d = 5 to 40:1, and the weight-average molecular weight is 5000 to 20000. More preferably, c is an integer from 150 to 250, d is an integer from 20 to 40, c:d = 8 to 25:1, and the weight-average molecular weight is 6000 to 15000. In some embodiments, c:d can be 15 to 60:1; in some specific embodiments, c is 200, d is 10, and c:d is 20:1.

[0038] In some embodiments, the phosphorylcholine derivative is one or more of 2-isocyanate ethyl phosphorylcholine, 2-epoxypropyloxyethyl phosphorylcholine, and 2-methacryloyloxyethyl phosphorylcholine. More preferably, it is 2-methacryloyloxyethyl phosphorylcholine.

[0039] In some embodiments, the molar ratio of the phosphorylcholine derivative, polydimethylsiloxane-amine, and triethylamine in step B) is 1:0.01-0.5:0.01-0.1. Preferably, it is 1:0.02-0.2:0.01-0.05, and more preferably 1:0.02-0.05:0.05. Specifically, it can be 1:0.1:0.03, 1:0.2:0.05, 1:0.3:0.07, 1:0.01:0.01, 1:0.05:0.02, 1:0.15:0.04, 1:0.25:0.06, 1:0.35:0.08, 1:0.4:0.09, or 1:0.5:0.1. Any intermediate ratio within the above range is acceptable, as long as the phosphorylcholine derivative is fully grafted onto the copolymer segments. Triethylamine also acts as an acid-binding agent to drive the reaction forward. The choice of protective gas is the same as in step A; any inert protective gas is suitable. In some embodiments, the protective gas in step B) is one of nitrogen, argon, helium, or neon.

[0040] The mass-to-volume ratio of the phosphorylcholine derivative to the solvent is 1g:15-20mL, preferably 1g:16-18mL, and more preferably 1g:17mL.

[0041] The solvent is one of anhydrous methanol, anhydrous ethanol, and trifluoroethanol, more preferably anhydrous ethanol. This ensures that all reactants are fully dissolved and dispersed. The reaction temperature is 50-70℃, preferably 52-60℃, more preferably 55℃; the reaction time is 12-24h, preferably 18-22h, more preferably 20h.

[0042] For example, the reaction can be carried out at 60℃ for 18 hours, 55℃ for 22 hours, or 65℃ for 15 hours. Within these temperature and time ranges, the active groups can be fully reacted, avoiding side reactions. After the reaction is complete, the reaction solution is added to acetone for precipitation. The precipitate is collected by filtration and washed with acetone 3-5 times to remove unreacted raw materials, preferably 4 times. Then, it is placed in a vacuum drying oven and dried at 50℃ to constant weight to obtain the purified phosphorylcholine siloxane copolymer.

[0043] The polydimethylsiloxane backbone also provides lubrication for the coating, while the reactive siloxane groups in the side chains can participate in cross-linking during film formation, further enhancing the coating's adhesion and structural stability.

[0044] The fluorinated siloxane copolymer obtained in step A) and the phosphorylcholine siloxane copolymer obtained in step B) are dissolved in a solvent and mixed to obtain an anti-adhesion and anticoagulant lubricating coating material.

[0045] The obtained fluorinated siloxane copolymer and phosphorylcholine siloxane copolymer are dissolved in a solvent and mixed evenly to obtain an anti-adhesion and anticoagulant lubricating coating material. The mass ratio of the fluorinated siloxane copolymer to the phosphorylcholine siloxane copolymer is 1:1.5, and the ratio can be adjusted according to the actual requirements for lubrication and anticoagulant properties. The solvent is preferably one or more of 1-chloro-3,3,3-trifluoropropene, isopropanol, heptane, and deionized water, preferably a mixture of 1-chloro-3,3,3-trifluoropropene and isopropanol.

[0046] This invention provides an anti-adhesion and anticoagulant lubricating coating material, which is prepared by any one of the preparation methods described in the above technical solutions.

[0047] The present invention also provides an anti-adhesion and anticoagulant lubricating coating material prepared by the above method, which combines the advantages of fluorinated segments, polydimethylsiloxane segments and phosphorylcholine groups through the compounding of two copolymers, thereby achieving excellent lubricity, antibacterial adhesion and anticoagulant properties.

[0048] This invention provides the application of the anti-adhesion and anticoagulant lubricating coating material prepared by any of the above-described preparation methods, or the anti-adhesion and anticoagulant lubricating coating material described in the above-described technical solutions, in the preparation of blood contact medical devices.

[0049] This invention also provides the application of the aforementioned anti-adhesion, anticoagulation, and lubricating coating material in the field of interventional medical devices. It can be coated onto the surface of the substrate of interventional medical devices by means of dip coating, drop coating, spray coating, etc. After being left to stand at room temperature or cured by heating, a stable cross-linked coating can be formed, giving the substrate excellent anti-adhesion, anticoagulation, and lubricating properties. It is especially suitable for metal medical devices and components such as puncture needles, which can effectively reduce puncture resistance and reduce the risk of infection and coagulation.

[0050] The metal medical devices and components described in this invention include, but are not limited to, hemodialysis needles, blood collection needles, and guide wires. The coating materials of this invention are also applicable to other metal devices in the field that require anti-adhesion, lubrication, and anticoagulation properties.

[0051] This invention, through molecular structure design and optimized component ratio control, endows the coating with highly efficient anticoagulant and anti-adhesion functions while maintaining excellent lubrication performance. Single-dip coating simplifies the coating process, and the cross-linking reaction between the coating and the metal surface enhances coating stability. Before and after entering the bloodstream, it can switch between dry lubrication and wet anticoagulant functions. Before entering the bloodstream, the phosphorylcholine siloxane segments contract, while the fluorinated siloxane segments exert lubrication and antibacterial adhesion functions. After entering the bloodstream, the fluorinated siloxane segments contract, while the phosphorylcholine siloxane segments exert anti-protein adhesion and anticoagulant functions. The friction coefficient on the surface of the metal catheter is 0.319, which is better than the 0.431 of the prior art. The puncture force of the hemodialysis needle is only 0.746N. This anti-adhesion and anticoagulant lubricating coating material has good antibacterial adhesion, anti-protein adhesion and anticoagulant properties. The antibacterial rate against Staphylococcus aureus is 99.9%, the BSA adhesion amount is 0.02μg / cm², and the blood coagulation index (BCI) can reach 112.85%.

[0052] The method for determining the friction coefficient of this invention is as follows: The metal-coated tube sample (if it is a hollow thin-walled tube, a suitable mandrel needs to be inserted for support) is vertically clamped on the equipment, so that the test section passes between two silicone sheets, and purified water at 37℃±2℃ is injected into the water tank. The clamping force is set to 1N, the running speed is 10 mm / s, and the test stroke is 30 mm. After the instrument is started, the silicone sheets clamp the sample with constant pressure, and the lifting device drives the sample to slide upward at a uniform speed. The sensor records the friction force during the sliding process and automatically calculates the friction coefficient. The average value is taken after 5 consecutive tests to evaluate the lubrication performance of the coating.

[0053] The method for determining the anti-adhesion and anticoagulant properties of the coating in this invention involves evaluating the antibacterial adhesion performance of the coating using a colony counting method. A 1 cm x 1 cm coated metal sheet is placed in a 24-well plate, and 10 μL of 10 μL of the solution is taken. 8 CFU / mL bacterial suspension was added dropwise to the surface of a metal plate, covered with a PE film (0.7cm x 0.7cm), and incubated at 37℃ for 4 h. The plate was then rinsed three times with 1 mL PBS solution. The metal plate and coated metal plate were placed in a centrifuge tube, 2 mL PBS was added, and the tube was sonicated for 2 minutes. 200 μL of the liquid from the centrifuge tube was transferred to a culture dish containing LB solid medium and incubated at 37℃ for 24 h. The culture dish was then removed, and the bacterial count was determined based on the plate-laying experiment photograph.

[0054] The concentration of fetal bovine serum albumin (BSA) adsorbed on the coated surface was determined using the Pierce Micro-BCA protein assay. A 1 cm x 1 cm coated metal sheet was soaked in PBS overnight and then placed in a 24-well plate. 2 mL of a 1 mg / mL BSA PBS solution was added to each well. After adsorption at 37°C for 1 day, the sheet was removed and washed three times with fresh PBS to remove physically adsorbed proteins. The sheet was then placed in a 1% SDS PBS solution and washed at 37°C for 1 hour to elute chemically adsorbed proteins. The protein concentration in the eluent was measured using a BCA assay kit, with OD values ​​read at 562 nm for comparison.

[0055] The blood coagulation index (BCI) assay used whole mouse blood containing an anticoagulant. A metal plate was placed in a petri dish. 50 μL of whole mouse blood and 5 μL of 0.2 M CaCl2 solution were added to both a plain metal plate and a coated metal plate. Blood was directly added to the petri dish without a metal plate as a positive control. The petri dishes were heated in a 37 °C water bath. After the blood coagulated at 37 °C for 5 minutes, 10 mL of deionized water was slowly added to the petri dish, and the dish was gently agitated. Hemoglobin from the uncoagulated red blood cells was released into the deionized water, turning the water red, thus stopping the coagulation. The intensity of the red color and the BCI value were observed to determine the in vitro hemostatic performance of the coated metal plate. The absorbance of the hemoglobin solution at 542 nm was measured to calculate the BCI of the sample.

[0056] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context.

[0057] The term "anti-adhesion" refers to resisting the adsorption and adhesion of substances such as bacteria, proteins, and blood cells on the coating surface, reducing the adhesion and accumulation of exogenous substances on the instrument surface, and lowering the risk of adverse reactions such as infection and thrombosis.

[0058] The term "anticoagulation" refers to inhibiting the activation of coagulation factors, platelet aggregation, and fibrin deposition in the blood, delaying the process of blood clotting on the contact surface of instruments, reducing thrombus formation, and lowering the probability of thromboembolic complications.

[0059] The term "lubricating coating" refers to a coating that reduces the coefficient of friction on the surface of an instrument, allowing the instrument to smoothly enter human tissue during interventional procedures, reducing scratching damage to the tissue, lowering operational resistance, and improving the safety and smoothness of the interventional procedure.

[0060] The term "blood contact medical device" refers to a medical device that needs to come into direct or indirect contact with human blood during use. These devices need to be in continuous or instantaneous contact with blood during use, so there are clear requirements for the anticoagulation and anti-adhesion properties of their surfaces to avoid adverse reactions such as coagulation and infection.

[0061] The terms “including,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood as open-ended and non-restrictive, for example, not excluding other unstated elements or steps, unless otherwise specifically stated or understood from the context.

[0062] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0063] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items.

[0064] It should be understood that the order of the steps or the order in which certain actions are performed is not important as long as the invention remains operational. Furthermore, two or more steps or actions can be performed simultaneously.

[0065] The use of any and all instances or exemplary language such as “e.g.” or “including” in this document is merely intended to better illustrate the invention and is not intended to limit the scope of the invention unless the claims are made. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of the invention.

[0066] Furthermore, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as precisely as possible. However, any value inevitably contains standard deviations due to individual test methods. Therefore, unless explicitly stated otherwise, it should be understood that all ranges, quantities, values, and percentages used in this disclosure are modified with the word "approximately". Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.

[0067] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0068] The embodiments and comparative examples of this invention describe some examples, in which the embodiments illustrate certain implementations of the invention. However, this does not mean that the effects of the invention can only be achieved in these examples.

[0069] To further illustrate the present invention, the following describes in detail, with reference to embodiments, an anti-adhesion and anticoagulant lubricating coating material provided by the present invention, its preparation method, and its application.

[0070] Example 1

[0071] Ethyl 1H, 1H, 2H, 2H-perfluorodecyl acrylate (PFDA), polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 10000), and triethylamine in a molar ratio of 1:2.5:0.03 were dissolved in toluene (PFDA to toluene mass-volume ratio 0.1 g: 40 mL) and added to a three-necked flask. The mixture was heated to 65 °C under N2 protection and maintained at this temperature for 12 h. After washing three times with deionized water, the mixture was rotary evaporated to obtain a fluorosiloxane copolymer. 2-Methacryloxyethylphosphorylcholine (MPC), polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 10000), and triethylamine in a molar ratio of 1:0.05:0.05 were dissolved in anhydrous ethanol (MPC to anhydrous ethanol...). The product (at a mass-to-volume ratio of 1 g: 17 mL) was added to a three-necked flask, heated to 55 °C under N2 protection, and kept at that temperature for 20 h. After precipitating and washing three times with acetone, the product was dried in a vacuum oven (50 °C) for 12 h to obtain the PDMS-g-MPC graft copolymer. The two products were dissolved in a mixture of 1-chloro-3,3,3-trifluoropropylene and isopropanol (volume ratio of 1-chloro-3,3,3-trifluoropropylene and isopropanol was 70:30) to obtain an anti-adhesion, anticoagulant, and lubricating coating material.

[0072] Figure 1 This is a schematic diagram of the anti-adhesion and anticoagulant lubricating coating prepared in Example 1, and its chain segment states before and after entering the blood (before and after entering the blood, it can switch between dry lubrication and wet anticoagulant functions. Before entering the blood, the phosphorylcholine siloxane chain segments contract, and the fluorinated siloxane chain segments perform lubrication and antibacterial adhesion functions. After entering the blood, the fluorinated siloxane chain segments contract, and the phosphorylcholine siloxane chain segments perform anti-protein adhesion and anticoagulant functions). The metal tube was immersed in the aforementioned anti-adhesion, anticoagulant, and lubricating coating material using a dip-coating method to form an anti-adhesion, anticoagulant, and lubricating coating on the metal surface, and its coefficient of friction was measured. The aforementioned anti-adhesion and anticoagulant coating material was then dropped onto the surface of a metal sheet (length × width = 1.0 × 1.0 cm) to form an anti-adhesion, anticoagulant, and lubricating coating, and its anti-adhesion and anticoagulant properties were measured. Specific results are shown in [link to results]. Figure 2-5 .

[0073] Depend on Figure 2 , Figure 3 It can be seen that the anti-adhesion and anticoagulant lubricating coating material of Example 1 has good lubrication performance.

[0074] Depend on Figure 4 It can be seen that the anti-adhesion and anticoagulant lubricating coating material of Example 1 has good antibacterial adhesion properties.

[0075] Depend on Figure 5 It can be seen that the anti-adhesion and anticoagulant lubricating coating material of Example 1 has good anti-protein adhesion properties.

[0076] Depend on Figure 6 It can be seen that the BCI value of the anti-adhesion and anticoagulant lubricating coating material of Example 1 is 112.85%, which indicates that it has good anticoagulant properties.

[0077] Example 2

[0078] Ethyl 1H, 1H, 2H, 2H-perfluorodecyl acrylate (PFDA), polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 5000), and triethylamine in a molar ratio of 1:2.5:0.03 were dissolved in toluene (PFDA to toluene mass-to-volume ratio of 0.1 g:40 mL) and added to a three-necked flask. The mixture was heated to 75 °C under N2 protection and maintained at this temperature for 10 h. After washing four times with deionized water, the fluorosiloxane copolymer was obtained by rotary evaporation. 2-Methacryloxyethylphosphorylcholine (MPC) and polydimethylsiloxane-amine (PDMS-amine) in a molar ratio of 1:0.05:0.05 were then added. MPC (weight average molecular weight of 15000) and triethylamine were dissolved in anhydrous ethanol (mass-volume ratio of MPC to anhydrous ethanol of 1 g: 17 mL) and added to a three-necked flask. The mixture was heated to 50 °C under N2 protection and kept at that temperature for 24 h. After precipitation and washing three times with acetone, the copolymer was dried in a vacuum oven (45 °C) for 16 h to obtain the copolymer. The two products were dissolved in a mixture of 1-chloro-3,3,3-trifluoropropene and isopropanol (volume ratio of 1-chloro-3,3,3-trifluoropropene to isopropanol of 70:30) to obtain an anti-adhesion, anticoagulant, and lubricating coating material.

[0079] Example 3

[0080] Dodecafluoroheptyl methacrylate, polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 8000), and triethylamine in a molar ratio of 1:2:0.03 were dissolved in toluene (PFDA to toluene mass-to-volume ratio of 0.1 g:40 mL) and added to a three-necked flask. The mixture was heated to 75 °C under N2 protection and maintained at this temperature for 10 h. After washing four times with deionized water, the fluorinated siloxane copolymer was obtained by rotary evaporation. A fluorosiloxane copolymer in a molar ratio of 1:0.04:0.04 was then added. Epioxypropyloxyethyl phosphorylcholine, polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight of 12000), and triethylamine were dissolved in anhydrous ethanol (the mass-volume ratio of MPC to anhydrous ethanol was 1 g: 17 mL) and added to a three-necked flask. The mixture was heated to 55 °C under N2 protection and kept at this temperature for 20 h. After precipitation and washing three times with acetone, the copolymer was dried in a vacuum oven (50 °C) for 12 h to obtain the copolymer. The two products were dissolved in a mixture of 1-chloro-3,3,3-trifluoropropylene and isopropanol (the volume ratio of 1-chloro-3,3,3-trifluoropropylene to isopropanol was 70:30) to obtain an anti-adhesion, anticoagulant, and lubricating coating material.

[0081] Example 4

[0082] A mixture of 1H,1H,2H,2H-heptadecane acrylate, polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 10000), and triethylamine in a molar ratio of 1:1:0.05 was dissolved in toluene (1H,1H,2H,2H-heptadecane acrylate to toluene mass-to-volume ratio of 0.1 g:20 mL) and added to a three-necked flask. The mixture was heated to 68 °C under N2 protection and maintained at this temperature for 10 h. After washing three times with deionized water, the mixture was rotary evaporated to obtain a fluorosiloxane copolymer. A mixture of 2-methacryloyloxyethylphosphorylcholine (MPC), polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 15000), and triethylamine in a molar ratio of 1:0.03:0.03 was dissolved in anhydrous ethanol. MPC and anhydrous ethanol (mass-volume ratio of 1 g: 17 mL) were added to a three-necked flask, heated to 55°C under N2 protection, and kept at this temperature for 20 h. After precipitation and washing three times with acetone, the PDMS-g-MPC graft copolymer was obtained by drying in a vacuum oven (50°C) for 12 h. The two products were dissolved in a mixture of 1-chloro-3,3,3-trifluoropropylene and isopropanol (volume ratio of 1-chloro-3,3,3-trifluoropropylene and isopropanol was 60:40) to obtain an anti-adhesion, anticoagulant, and lubricating coating material.

[0083] Example 5

[0084] Ethyl 1H, 1H, 2H, 2H-perfluorodecyl acrylate (PFDA), polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 8000), and triethylamine in a molar ratio of 1:2:0.05 were dissolved in toluene (PFDA to toluene mass-volume ratio 0.1 g: 30 mL) and added to a three-necked flask. The mixture was heated to 70 °C under N2 protection and maintained at this temperature for 12 h. After washing three times with deionized water, the fluorosiloxane copolymer was obtained by rotary evaporation. 2- Ethylphosphonic choline isocyanate, polydimethylsiloxane-amine (PDMS-amine) (weight average molecular weight 8000), and triethylamine were dissolved in anhydrous ethanol (MPC to anhydrous ethanol mass-volume ratio of 1 g: 20 mL) and added to a three-necked flask. The mixture was heated to 52 °C under N2 protection and kept at this temperature for 20 h. After precipitation and washing three times with acetone, the copolymer was dried in a vacuum oven (50 °C) for 12 h to obtain the copolymer. The two products were dissolved in a mixture of 1-chloro-3,3,3-trifluoropropene and isopropanol (1-chloro-3,3,3-trifluoropropene to isopropanol volume ratio of 70:30) to obtain an anti-adhesion, anticoagulant, and lubricating coating material.

[0085] Comparative Example 1

[0086] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that no fluorinated siloxane copolymer was added. Before entering the bloodstream, the phosphorylcholine siloxane segments contracted, and no fluorinated siloxane segments exerted lubrication and antibacterial adhesion functions. After entering the bloodstream, the phosphorylcholine siloxane segments exerted anti-protein adhesion and anticoagulant functions. Plate-layout tests showed that the anti-adhesion coating surface tested positive for 6 × 10⁻⁶ mm. 4 CFU / cm 2 The presence of live bacteria indicates poor antibacterial adhesion properties of the coating. A coefficient of friction of 0.626 and a puncture force of 1.243 N indicate poor lubrication of the coating. In the BSA adhesion test, the amount of protein adhered was 0.03 μg / cm², indicating good anti-protein adhesion properties of the coating. In the in vitro coagulation test, the coagulation index was 110.66%, indicating excellent anticoagulant properties of the coating.

[0087] Comparative Example 2

[0088] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that phosphorylcholine siloxane copolymer was not added. Before entering the bloodstream, the fluorinated siloxane segments exerted lubricating and antibacterial adhesion functions. After entering the bloodstream, the fluorinated siloxane segments contracted, and the phosphorylcholine-free siloxane segments exerted anti-protein adhesion and anticoagulant functions. Plate-layout experiments showed that the antibacterial adhesion coating surface exhibited a density of 1.8 × 10⁻⁶. 2 CFU / cm 2The presence of live bacteria indicates that the coating has a certain antibacterial adhesion effect. A coefficient of friction of 0.416 and a puncture force of 0.810 N indicate good lubrication properties. The BSA adhesion test showed a protein adhesion amount of 0.43 μg / cm², indicating poor anti-protein adhesion performance of the coating. The in vitro coagulation test showed a coagulation index of 48.42%, indicating that the coating has no anticoagulant properties but possesses certain hemostatic properties.

[0089] Comparative Example 3

[0090] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method in Example 1, except that the molar ratio of 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA) and polydimethylsiloxane-amine (PDMS-amine) was 1:15. The antibacterial adhesion test on the coating surface showed a result of 2.2 × 10⁻⁶. 3 CFU / cm 2 The presence of live bacteria indicates that the coating has poor antibacterial adhesion properties. The BSA adhesion test showed that the amount of protein adhesion was 0.03 μg / cm², indicating that the coating has good anti-protein adhesion properties. The in vitro coagulation test showed that the coagulation index was 109.42%, indicating that the coating has excellent anticoagulant properties.

[0091] Comparative Example 4

[0092] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method in Example 1, except that the molar ratio of 1H, 1H, 2H, 2H-perfluorodecyl acrylate (PFDA) and polydimethylsiloxane-amine (PDMS-amine) was 1:30. The prepared anti-adhesion and anticoagulant lubricating coating material had poor solubility in the solvent, the solution was unstable, and it was prone to precipitation.

[0093] Comparative Example 5

[0094] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method in Example 1, except that the molar ratio of 2-methacryloyloxyethyl phosphorylcholine (MPC) to polydimethylsiloxane-amine was 1:1. In the slab laying test, no viable bacteria were detected on the coating surface in the antibacterial adhesion test, indicating that the coating has good antibacterial adhesion properties. However, in the BSA adhesion test, the protein adhesion amount was 0.36 μg / cm², and in the in vitro coagulation test, the coagulation index was 71.44%, indicating that the coating has poor anti-protein adhesion and anticoagulant properties.

[0095] Comparative Example 6

[0096] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method in Example 1, except that the molar ratio of 2-methacryloyloxyethyl phosphorylcholine (MPC) to polydimethylsiloxane-amine was 1:0.005. The coating peeled off upon immersion in an aqueous phase, indicating poor water resistance.

[0097] Comparative Example 7

[0098] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that the fluorinated acrylate monomer was perfluorobutyl ethyl acrylate. The antibacterial adhesion test showed that the coating surface had a surface area of ​​4.8 × 10⁻⁶. 3 CFU / cm 2 The presence of live bacteria indicates that the coating has poor antibacterial adhesion. In the BSA adhesion test, the amount of protein adhered was 0.08 μg / cm², indicating that the coating has some anti-protein adhesion properties. In the in vitro coagulation test, the coagulation index was 100.22%, indicating that the coating has excellent anticoagulant properties.

[0099] Comparative Example 8

[0100] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that the fluorinated acrylate monomer was a perfluoropolyether acrylate. Microphase separation occurred in the copolymer solution, resulting in poor surface uniformity after coating ("orange peel" defect), a coating friction coefficient of 0.563, and poor lubrication performance.

[0101] Comparative Example 9

[0102] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that the phosphorylcholine derivative was methacryloyloxyhexylphosphoniccholine. In the plating test, no viable bacteria were detected on the coating surface in the antibacterial adhesion test, indicating that the coating has good antibacterial adhesion properties. However, in the BSA adhesion test, the protein adhesion amount was 0.30 μg / cm², and in the in vitro coagulation test, the coagulation index was 69.24%, indicating that the coating has poor anti-protein adhesion and anticoagulant properties.

[0103] Comparative Example 10

[0104] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that the phosphorylcholine derivative was acrylamide phosphorylcholine (APC). In the slab laying test, no viable bacteria were detected on the coating surface in the antibacterial adhesion test, indicating that the coating has good antibacterial adhesion properties. However, in the BSA adhesion test, the protein adhesion amount was 0.26 μg / cm², and in the in vitro coagulation test, the coagulation index was 52.24%, indicating that the coating has poor anti-protein adhesion and anticoagulant properties. The coating swells upon immersion in an aqueous phase, indicating that the coating has poor water resistance.

[0105] Comparative Example 11

[0106] An anti-adhesion and anticoagulant lubricating coating material was prepared according to the method of Example 1, except that the fluorinated acrylate monomer was perfluorobutyl ethyl acrylate, and the phosphorylcholine derivative was methacryloyloxyhexyl phosphorylcholine. The anti-adhesion coating surface showed a viscosity of 5.6 × 10⁻⁶ ppm in a slab laying test. 3 CFU / cm 2 The presence of live bacteria indicates that the coating has poor antibacterial adhesion properties. The BSA adhesion test showed a protein adhesion amount of 0.33 μg / cm², and the in vitro coagulation test showed a coagulation index of 67.64%, indicating that the coating has poor resistance to protein adhesion and anticoagulation properties.

[0107] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an anti-adhesion, anticoagulant, lubricating coating material, characterized in that, Includes the following steps: A) Under a protective gas atmosphere, a fluorinated acrylate monomer of formula (I), a polydimethylsiloxane-amine of formula (II), triethylamine and a solvent are mixed and reacted to obtain a fluorinated siloxane copolymer; B) Under a protective gas atmosphere, the phosphorylcholine derivative of formula (III), the polydimethylsiloxane-amine of formula (IV), triethylamine and solvent are mixed and reacted, and the precipitate is washed and dried to obtain the phosphorylcholine siloxane copolymer. C) Dissolve the fluorinated siloxane copolymer obtained in step A) and the phosphorylcholine siloxane copolymer obtained in step B) in a solvent, and mix them to obtain an anti-adhesion and anticoagulant lubricating coating material; Formula (I); Formula (II); Formula (III); Formula (IV); Where R represents H or CH3, m≥1, n≥1; R1 and R2 independently represent H or OCH3, A independently represents a group containing an amino group, a is an integer from 30 to 300, b is an integer from 1 to 100, a:b=5~100:1, and the weight-average molecular weight is 1000~20000; R5 represents an epoxy group, isocyanate group, or acryloyl group, R3 and R4 independently represent H or OCH3, B independently represents a group containing an amino group, c is an integer from 50 to 400, d is an integer from 5 to 150, c:d=5~100:1, and the weight-average molecular weight is 3000~30000.

2. The preparation method according to claim 1, characterized in that, The fluorinated acrylate monomers are one or more of the following: dodecafluoroheptyl methacrylate, 1H,1H,2H,2H-heptadecane acrylate, and 1H,1H,2H,2H-perfluorodecyl acrylate.

3. The preparation method according to claim 1, characterized in that, In step A), the molar ratio of the fluorinated acrylate monomer, polydimethylsiloxane-amine, and triethylamine is 1:1~20:0.01~0.

1.

4. The preparation method according to claim 1, characterized in that, The protective gas in step A) is one of nitrogen, argon, helium, or neon; The solvent is one of tetrahydrofuran, toluene, ethanol, and acetone; The reaction temperature is 60~80℃ and the reaction time is 6~12h; the reaction is followed by washing and rotary evaporation; the washing solvent is deionized water.

5. The preparation method according to claim 1, characterized in that, Step B) The phosphorylcholine derivative is one or more of 2-isocyanate ethyl phosphorylcholine, 2-epoxypropyloxyethyl phosphorylcholine and 2-methacryloyloxyethyl phosphorylcholine.

6. The preparation method according to claim 1, characterized in that, In step B), the molar ratio of the phosphorylcholine derivative, polydimethylsiloxane-amine, and triethylamine is 1:0.01-0.5:0.01~0.

1.

7. The preparation method according to claim 1, characterized in that, The protective gas mentioned in step B) is one of nitrogen, argon, helium, and neon; The solvent is one of anhydrous methanol, anhydrous ethanol, and trifluoroethanol; the reaction temperature is 50~70℃, and the reaction time is 12~24h; the washing reagent is acetone, and the washing is performed 3~5 times.

8. The preparation method according to claim 1, characterized in that, The mass ratio of the fluorinated siloxane copolymer obtained in step C) to the phosphorylcholine siloxane copolymer obtained in step B) is 1:1.

5.

9. An anti-adhesion, anticoagulant, lubricating coating material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the anti-adhesion and anticoagulant lubricating coating material prepared by the preparation method according to any one of claims 1 to 8 or the anti-adhesion and anticoagulant lubricating coating material according to claim 9 in the preparation of blood contact medical devices.

Citation Information

Patent Citations

  • An anticoagulant polymer coating material and its preparation method

    CN113372494B